Army Human Resources Development Strategy through Human Capital Approach - Purwanto, Sigit; Ilhamsyah, Irfan (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
The focus of research on the statement is the strategy of developing human resources (HR) of the Army through a human capital approach in increasing the professionalism, capability, and effectiveness of military personnel to support the operational success of the Army in facing various security challenges. The purpose of this research is to analyze the Human Resource Development Strategy of the Indonesian Army through the Human Capital Approach.  The method used in this research is descriptive qualitative with SWOT analysis tools and tree analysis. The theory used in this research is human capital. The results showed that the strategies used for HR development with a human capital approach are (1) Improving the quality of education and training of soldiers through evaluation and inclusive curriculum development. (2) Utilizing good education and training to improve soldiers' capabilities through an integrated and sustainable human capital approach. (3) Improving the professionalism of soldiers through merit-based personnel management system reform. (4) Improving soldiers' welfare by providing access to specialized higher education through the Defense University. (5) Improving transparency and efficiency through information and communication technology, keeping soldiers' focus on the main task of defense. By adopting a human capital approach, the Army is expected to improve the quality and capability of soldiers, so that they are ready to face future challenges and support the achievement of the organization's strategic goals.